Media, Information, Disinformation, and Propaganda in the Context of the Russo-Ukrainian Conflict - Marsili, M. (13rd edition of the international scientific media conference, 2022)
Lecture on the current situation on and around media, information, disinformation, and propaganda in the context of the Russo-Ukrainian conflict and in perspective given as keynote speaker in the plenary session of the 13th edition of the international scientific media conference “War Media Challenges: Media, Information, Disinformation, Propaganda”, held at the University of Bielsko-Biała, Poland, on 18 November 2022.